THE CURRENT SITUATION AND TRENDS OF NON-BANK MICROCREDITING IN UKRAINE - Shuplat , O. M. (The actual problems of regional economy development, 2019)
Research objective: Identify problems and substantiate ways to develop the non-bank microcredit market in Ukraine. The set of methods of scientific knowledge, including methods of scientific abstraction and logical-dialectical (in the study of the content of microcredit) are applied in the work; statistical and graphical analysis - for analysis, comparison and visualization of statistics (in the process of researching current trends of the national micro-credit market) and empirical research methods. The essential characteristics of microcredit have been clarified and its role in consumer lending has been defined. The main factors that negatively influence the creation of an effective and high-quality non-bank micro-credit market in Ukraine are highlighted, and state levers are proposed to increase the attractiveness, transparency and reduce the risks of the non-bank micro-credit market. In turn, this will have a positive effect on the country's economic development, social well-being and private financial stability of the population. The paper on "The current state and trends of non-bank microcredit in Ukraine" substantiates the main directions of regulation of non-bank microcredit in consumer lending to economic entities in conditions of socio-economic instability. This will create favorable regulatory and institutional support for the non-bank microcredit market.